Architecture and Learning - The role of physical space in educational settings - Bergström, Jonas; Lindberg, Angelica (My University, 2020)
The engineering education is in the midst of transformation, and with that, a need for new learning environments arises. This study investigates the impact of the physical space on perceived learning, through the perspective of engineering students in higher education. It uses the lens of Challenge-based Learning in the strive to give recommendations for the future design of learning environments. To accomplish this goal, an engineering course was followed and assessed using direct observations, student and instructor surveys, and a student focus group interview. The questions were designed around planning and execution for the instructor surveys, and identified environmental factors of the physical space as well as defined learning for the student surveys and interview. The observations were used to document the factors of the physical space and the use of, and activities taking place within, the physical learning environment. The results of the study indicated an effect of physical space on perceived learning, where specific factors showed to influence specific parts of the defined learning. It was concluded that the physical space was one of three actors with power to influence learning, with the other two being identified as pedagogy and instructor. This study emphasises the importance of considering what type of learning is intended for the physical learning spaces, both in architectural design and evaluation, as the interaction between pedagogy and space was the focal point of the conclusion.
Keywords: space; perceived learning; engineering; education; CBL; learning environment; pedagogy; instructor; architecture; design